2018
DOI: 10.1007/s00190-018-1204-5
|View full text |Cite
|
Sign up to set email alerts
|

Modernizing and expanding the NASA Space Geodesy Network to meet future geodetic requirements

Abstract: NASA maintains and operates a global network of Very Long Baseline Interferometry (VLBI), Satellite Laser Ranging (SLR), and Global Navigation Satellite System ground stations as part of the NASA Space Geodesy Program. The NASA Space Geodesy Network (NSGN) provides the geodetic products that support Earth observations and the related science requirements as outlined by the US National Research Council (NRC in Precise geodetic infrastructure: national requirements for a shared resource, National Academies Press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…Lösler et al (2019) measured the change in the shape of one of the 13.2 m VGOS antennas at the Onsala Space Observatory (OSO), Sweden, and found that the change in delay from 5° to 90° elevation angles is less than 1 mm, which would result in a vertical height error of less than 1 mm. Finite element modeling by the manufacturer of the new 12 m VGOS antenna at McDonald Observatory, Texas (Merkowitz et al 2018), which is identical to KOKEE12M, indicated that it should also have a sub-millimeter change in delay over the observing range for geodetic observations.…”
Section: Kokee12m Gravitational Deformationmentioning
confidence: 99%
“…Lösler et al (2019) measured the change in the shape of one of the 13.2 m VGOS antennas at the Onsala Space Observatory (OSO), Sweden, and found that the change in delay from 5° to 90° elevation angles is less than 1 mm, which would result in a vertical height error of less than 1 mm. Finite element modeling by the manufacturer of the new 12 m VGOS antenna at McDonald Observatory, Texas (Merkowitz et al 2018), which is identical to KOKEE12M, indicated that it should also have a sub-millimeter change in delay over the observing range for geodetic observations.…”
Section: Kokee12m Gravitational Deformationmentioning
confidence: 99%
“…For any system data-related hardware upgrade, the ILRS has a minimum requirement of 20 LAGEOS and LAGEOS 2 passes along with 20 LARES satellite passes for QC analyses by the Analysis Standing Committee (ASC) (Otsubo et al 2018). The NASA Space Geodesy Project (SGP) (Merkowitz et al 2018) has established a more stringent longer duration (six or more months) testing, and the concurrent data generation capability easily supported such a long-term data comparison with no impact on the operational data. During the data gathering phase, the engineering analysis was performed periodically by Cybioms, using the full rate and the NP data.…”
Section: Ilrs Data Analysis For Station Qualificationmentioning
confidence: 99%
“…Создание единой координатной системы на территории разного масштаба отдельного государства, континента и всей Земли в целом входит в задачи космического геодезического обеспечения (Merkowitz et al, 2019). Применительно к геодезическому обеспечению космических исследований развитие получили специальные геодезические сети для космических исследований (Merkowitz, 2019).…”
Section: обсуждение и результатыunclassified